2012
DOI: 10.1128/aac.05913-11
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Ertapenem for Treatment of Bloodstream Infections Caused by Extended-Spectrum-β-Lactamase-Producing Enterobacteriaceae

Abstract: e Ertapenem is active against extended-spectrum-␤-lactamase (ESBL)-producing Enterobacteriaceae organisms but inactive against Pseudomonas aeruginosa and Acinetobacter baumannii. Due to a lack of therapeutic data for ertapenem in the treatment of ESBL bloodstream infections (BSIs), group 2 carbapenems (e.g., imipenem or meropenem) are often preferred for treatment of ESBL-producing Enterobacteriaceae, although their antipseudomonal activity is unnecessary. From 2005 to 2010, 261 patients with ESBL BSIs were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 31 publications
0
38
0
4
Order By: Relevance
“…Most studies evaluated imipenem or meropenem, but some experiences with ertapenem are also reported, especially as empirical therapy in community-acquired severe infections when coverage against Pseudomonas aeruginosa or Acinetobacter baumannii is not needed [46]. Some concerns are rising regarding the resistance to ertapenem in some Klebsiella and Enterobacter due to concurrent loss of porins [47,48].…”
Section: Role Of Carbapenemsmentioning
confidence: 95%
“…Most studies evaluated imipenem or meropenem, but some experiences with ertapenem are also reported, especially as empirical therapy in community-acquired severe infections when coverage against Pseudomonas aeruginosa or Acinetobacter baumannii is not needed [46]. Some concerns are rising regarding the resistance to ertapenem in some Klebsiella and Enterobacter due to concurrent loss of porins [47,48].…”
Section: Role Of Carbapenemsmentioning
confidence: 95%
“…Interestingly, the interpretation error rates for ESBL and AmpC resistotypes were also significantly increased for ertapenem (Table 1), despite the fact that ertapenem is considered a therapy of choice for ESBL and AmpC producers (32). For E. coli, 79% of all expected ertapenem interpretation errors were caused by the ESBL resistotype (Table 1).…”
Section: Fig 1 Schematic Representation Of Variables Influencing Intementioning
confidence: 99%
“…[1]. The isolation rate of resistant bacteria in BSIs has increased significantly with the rampant use of beta-lactams and aminoglycoside antibiotics, as well as the development of more invasive procedures and treatments [2]. The Chinese Ministry of Health National Antimicrobial Resistance Investigation Net annual reports of 2010 and 2011 estimated that the isolation rate of K. pneumoniae, which has become one of the most common pathogenic bacteria in BSIs, was 7.7% and 8.3%, respectively [3,4].…”
Section: Introductionmentioning
confidence: 99%